Transition probabilities between the X3Π, A3Σ−, B3Σ+, C3Π, D3Δ, and E3Π states of SiC molecules. (April 2019) - Xing, Wei; Shi, Deheng; Sun, Jinfeng
Highlights: Emissions of the D 3 Δ–C 3 Π and E 3 Π–D 3 Δ systems are weak. Lifetimes are approximately 10 −6 to 10 −7 s for the C 3 Π and E 3 Π states. Lifetimes are about 10 −5 s for the A 3 Σ − state and 10 −5 –10 −6 s for the B 3 Σ + state. A 3 Σ − –X 3 Π, B 3 Σ + –X 3 Π, C 3 Π–X 3 Π, C 3 Π–A 3 Σ −, D 3 Δ–X 3 Π, and E 3 Π–X 3 Π transitions are strong. Lifetimes of the D 3 Δ state vary in the range of 10 −3 –10 −5 s. Abstract: In this study, we calculated the potential energy curves of the X 3 Π, A 3 Σ −, B 3 Σ +, C 3 Π, D 3 Δ, and E 3 Π states of SiC molecules and the transition probabilities between them. The rotationless radiative lifetimes of the vibrational levels are in the order of 10 −5 s for the A 3 Σ − state, 10 −5 –10 −6 s for the B 3 Σ + state, and 10 −6 to 10 −7 s for the C 3 Π and E 3 Π states. This suggests that the spontaneous emissions originating from these states can easily occur. The rotationless radiative lifetimes vary in the range of 10 −3 –10 −5 s for the vibrational levels of the D 3 Δ state. The lifetime of the D 3 Δ state rapidly decreases with the increasing vibrational level, indicating that the occurrence of spontaneous emissions originating from this state at lower levels is more inhibited than those at higher levels. The emissions of the A 3 Σ − –X 3 Π, B 3 Σ + –X 3 Π, C 3 Π–X 3 Π, C 3 Π–A 3 Σ −, D 3 Δ–X 3 Π, and E 3 Π–X 3 Π system are strong, suggesting that these transitions can be measured easily by spectroscopy. The emissions of the D 3 Δ–C 3 Π and E 3 Π–D 3 Δ systems are weak, suggesting that these transitions are difficult to detect by spectroscopy. The spectral range of the strong emissions from the A 3 Σ − –X 3 Π system is in the infrared region. The strong emissions of the B 3 Σ + –X 3 Π, C 3 Π–X 3 Π, and C 3 Π–A 3 Σ − systems are of visible light. Some of these strong emissions, especially those from the A 3 Σ − –X 3 Π system, could be expected to be detectable in carbon star IRC + 10, 126 and the circumstellar shell. Graphical abstract: Image, graphical abstract The lifetimes are in the order of 10 −5 s for the A 3 Σ − state, 10 −5 –10 −6 s for the B 3 Σ + state, and 10 −6 to 10 −7 s for the C 3 Π and E 3 Π states of the SiC radical. This suggests that the spontaneous emissions originating from these states can occur easily. The lifetime varies in the range of 10 −3 –10 −5 s for the D 3 Δ state. The lifetime of the D 3 Δ state rapidly decreases with the increasing vibrational level. Overall, the A 3 Σ − –X 3 Π, B 3 Σ + –X 3 Π, C 3 Π–X 3 Π, C 3 Π– A 3 Σ −, D 3 Δ–X 3 Π, and E 3 Π– X 3 Π transitions are strong, while the D 3 Δ–C 3 Π and E 3 Π–D 3 Δ transitions are weak, suggesting that they are difficult to be detected via spectroscopy.